Validation of risk assessment scales and predictors of intentions to quit smoking in Australian Aboriginal and Torres Strait Islander peoples: a cross-sectional survey protocol - Gould, Gillian Sandra (BMJ Publishing Group, 2014)
INTRODUCTION: Tobacco smoking is a very significant behavioural risk factor for the health of Australian Aboriginal and Torres Strait Islanders, and is embedded as a social norm. With a focus on women of childbearing age, and men of similar age, this project aims to determine how Aboriginal and Torres Strait Islander smokers assess smoking risks and how these assessments contribute to their intentions to quit. The findings from this pragmatic study should contribute to developing culturally targeted interventions. METHODS AND ANALYSIS: A cross-sectional study using quantitative and qualitative data. A total of 120 Aboriginal and Torres Strait Islander community members aged 18–45 years will be recruited at community events and through an Aboriginal Community Controlled Health Service (ACCHS). Participants will be interviewed using a tablet computer or paper survey. The survey instrument uses modified risk behaviour scales, that is, the Risk Behaviour Diagnosis (RBD) scale and the Smoking Risk Assessment Target (SRAT) (adapted from the Risk Acceptance Ladder) to determine whether attitudes of Aboriginal and Torres Strait Islander smokers to health risk messages are predictors of intentions to quit smoking. The questionnaire will be assessed for face and content validity with a panel of Indigenous community members. The internal consistency of the RBD subscales and their patterns of correlation will be explored. Multivariate analyses will examine predictors of intentions to quit. This will include demographics such as age, gender, nicotine dependence, household smoking rules and perceived threat from smoking and efficacy for quitting. The two risk-assessment scales will be examined to see whether participant responses are correlated. ETHICS AND DISSEMINATION: The Aboriginal Health & Medical Research Council Ethics Committee and university ethics committees approved the study. The results will be published in a peer-reviewed journal and a community report will be disseminated by the ACCHS, and at community forums. NOTE ABOUT TERMINOLOGY: We use the term Aboriginal and Torres Strait Islander peoples, except where previous research has reported findings from only one group for example, Aboriginal people. Indigenous is used here to refer to Indigenous peoples in the international context, and issues, policies or systems, for example, Indigenous health, Indigenous tobacco control.